2016
DOI: 10.1161/strokeaha.116.013719
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Biomarkers in Childhood Arterial Ischemic Stroke

Abstract: Background and Purpose Among children with arterial ischemic stroke (AIS), those with arteriopathy have the highest recurrence risk. We hypothesized that arteriopathy progression is an inflammatory process, and that inflammatory biomarkers would predict recurrent AIS. Methods In an international study of childhood AIS, we selected cases classified into one of the three most common childhood AIS etiologies: definite arteriopathic (N=103), cardioembolic (N=55), or idiopathic (N=78). We measured serum concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 31 publications
(47 reference statements)
2
32
0
Order By: Relevance
“…7,9,17,18 Classical determinants for stroke and biomarkers reflecting endothelial injury and repair can also predict outcome. 17,19,20,21 There is also a trend for a better outcome 6 and few recurrences 17 in children treated with aspirin. In our former report of TCA, recurrence occurred in 3 of 4 children without treatment versus only one of 11 who received aspirin.…”
mentioning
confidence: 99%
“…7,9,17,18 Classical determinants for stroke and biomarkers reflecting endothelial injury and repair can also predict outcome. 17,19,20,21 There is also a trend for a better outcome 6 and few recurrences 17 in children treated with aspirin. In our former report of TCA, recurrence occurred in 3 of 4 children without treatment versus only one of 11 who received aspirin.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Prior diagnoses in children with symptomatic AIS are multiple and include cardiac disorders, haematological conditions (sickle cell anaemia, prothrombotic disorders), collagen tissue diseases, metabolic disorders, other chronic diseases, and acute illnesses. [6][7][8] Childhood infections, including Varicella Zoster virus, have been shown to be associated with an increased risk of AIS, with routine vaccinations being protective against AIS. 9,10 In addition, the presence of prothrombotic risk factors has been found in small case series and case control studies to be associated with ischaemic stroke in children, with this association confirmed by meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20] Several of these studies have identified vasculopathy, in particular moyamoya, as an important factor in predicting recurrent stroke. 8,15,20 There are some early data to suggest that prothrombotic states may also enhance the risk of recurrence, but many of these studies are limited by size and scope. 7,11,15,16,21 We therefore investigated in an international cohort study the relevance of prothrombotic risk factors, as well as underlying stroke subtypes, to a second stroke in paediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…2 The condition appears to have an inflammatory component: levels of serum inflammatory markers among children with arteriopathy predict recurrence. 3 Prior research has suggested that herpesvirus infections, and particularly varicella zoster virus (VZV), cause progressive cerebral vasculopathy. 4 In recent work from VIPS, moreover, herpesviruses other than VZV were also associated with stroke of multiple etiologies.…”
mentioning
confidence: 99%